Improving The Operation & Maintenance Performance of BDG CO2 Removal Plant Using Multi-Criteria Decision-Making Approach - Hariz , Luthfi; Hermawan , Pri (Jurnal Economic Resource, 2025)
BDG CO2 removal plant, serving as a gas purification facility, is one of the backbones for Pertamina EP Zone 7. Finding the best operation and maintenance (O&M) strategy is challenging due to the numerous factors that must be considered and the alternative solutions themselves which are not readily available at that point. This final project aims to propose a strategy to improve the O&M performance by finding the best alternative of O&M method by implementing a multi-criteria decision-making (MCDM) approach. Experts and decision makers are involved for identification of important factors, gathering ideas and opportunities. Alternatives are generated by implementing value-focused thinking (VFT) to ensure a structured and objective decision-making process that prioritizes values and fundamental objectives. The VFT resulting in 3 potential alternatives, namely Full-Coverage Service Contract with enhancement on maintenance, Full-Coverage Service Contract with enhancement on plant optimization and Full-Coverage Service Contract with enhancement on CO2 quality. The AHP method is applied to assess these alternatives based on criteria generated from semi-structured interview with decision makers and FGD with experts, these criteria are O&M Cost, Performance, Revenue and Compliance. The analysis reveals that Full-Coverage Service Contract with enhancement on plant optimization is the most appropriate solution